2017
DOI: 10.3390/rs9070648
|View full text |Cite|
|
Sign up to set email alerts
|

On the Design of Radar Corner Reflectors for Deformation Monitoring in Multi-Frequency InSAR

Abstract: Trihedral corner reflectors are being increasingly used as point targets in deformation monitoring studies using interferometric synthetic aperture radar (InSAR) techniques. The frequency and size dependence of the corner reflector Radar Cross Section (RCS) means that no single design can perform equally in all the possible imaging modes and radar frequencies available on the currently orbiting Synthetic Aperture Radar (SAR) satellites. Therefore, either a corner reflector design tailored to a specific data ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
83
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 26 publications
2
83
0
2
Order By: Relevance
“…As expected, the measured RCS are smaller than the theoretical ones. Several factors which can introduce a loss of RCS compared to the theoretical value are listed in [4]. A RCS loss exceeding 10 dB can result from a 5 mm plate curvature in a 1.0 m trihedral CR in X-band [27].…”
Section: Discussionmentioning
confidence: 99%
“…As expected, the measured RCS are smaller than the theoretical ones. Several factors which can introduce a loss of RCS compared to the theoretical value are listed in [4]. A RCS loss exceeding 10 dB can result from a 5 mm plate curvature in a 1.0 m trihedral CR in X-band [27].…”
Section: Discussionmentioning
confidence: 99%
“…MTI techniques can be grouped in two main classes: Persistent Scatterers (PS) [39] or Small BAseline Subsets (SBAS) [40] to deliver displacements along the Line Of Sight (LOS) direction with accuracy in the order of a few millimeters per year [41]. Whilst building or infrastructure is taken as PS in urban areas [42], artificial Corner Reflectors (CRs) were installed to investigate areas characterized by low interferometric coherence or when a point wise analysis is foreseen [43][44][45][46][47][48][49]. Notti et al [50] demonstrated the potential of X-band SAR data using TerraSAR-X for landslide mapping and monitoring but a few natural PS were found in mountainous areas.…”
Section: Introductionmentioning
confidence: 99%
“…Corner reflectors are important for various applications in a SAR sensor's lifecycle. Consequently, Garthwaite discusses design considerations for corner reflectors used for deformation monitoring [2]. In an interesting piece on interferences, Monti-Guarnieri et al [3] present their work on the radio frequency interferences in C-band based on an analysis of the first 8-10 echo measurements per burst to provide a first radio frequency interference map over Europe.…”
mentioning
confidence: 99%